On the energy and pseudo-angle of Frenet vector fields in R^n_v - Altin, A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In this paper, we compute the energy of a Frenet vector field and the pseudo-angle between Frenet vectors for a given non-null curve C in semi-Euclidean space of signature (n, v). It is shown that the energy and pseudo-angle can be expressed in terms of the curvature functions of C.